A novel nano interface for particulate‐reinforced titanium matrix composites. Issue 1 (24th September 2021) - Chen, Hao; Gui, Zhenzhen; Wang, Xinyun; Gao, Xianhui; Liu, Dejian
Abstract: The WC/W2 C eutectic reinforecement was applied to suppress the formation of interfacial reaction layer TiC in titanium matrix composites due to the lower interfacial reactivity between W2 C and Ti. W solid solution interface was successfully produced at the WC/Ti interface, while the most readily formed compact reaction layer TiC was completely delimitated. Such W solid solution interface is more effective to transfer stress from the matrix to the particles than that of the TiC layer. Decohesion of the W interface was never occurred. Abstract : Nano W(Ti) solid solution bonding is successfully achieved for Ti metal matrix and WC ceramic reinforcement. Such nano W(Ti) interface exhibits ultrahigh bonding strength and excellent toughness in comparasion with the traditional brittle compound reaction layer. The strength and strain of the produced composites is increased to almost two times (from 470 MPa to 920Mpa) and 11 times (from 0.5% to 5.5%), respectively.